The sum of the present ages of a father and his son is 60 years. Six years ago, father’s age was five times the age of the son. After 6 years, son’s age will be:
👨👦 Father-Son Age Puzzle 👦
Let’s break it down step by step:
Present ages:
Father’s age = F
Son’s age = S
The sum of their present ages is 60:
F + S = 60
Six years ago:
Father’s age = F – 6
Son’s age = S – 6
At that time, the father’s age was five times the son’s age:
F – 6 = 5(S – 6)
Simplify the equation:
F – 6 = 5S – 30
F = 5S – 24
Now, substitute this expression for F into the first equation:
(5S – 24) + S = 60
Combine like terms:
6S – 24 = 60
Add 24 to both sides:
6S = 84
Divide by 6:
S = 14
Now, find the son’s age after 6 years:
Son’s age after 6 years = S + 6
= 14 + 6
= 20
The son’s age after 6 years will be 20.